The Seven Cooperative Principles and Legal Regulations for the Establishment and Operation of Cooperatives in the Agricultural and Food Sector in Poland - Suchoń, Aneta (PRAWO i WIĘŹ, 2025)
The objective of this paper is to determine whether and to what extent the regulations governing the establishment and operation of selected cooperatives in the agri-food sector in Poland take into account, implement and apply the cooperative principles of the ICA. Due to the broad scope of the topic and the richness of the legislative material, only selected issues are presented. Within the article, the author analyses the various cooperative principles (Voluntary and open membership, Democratic member control, Economic participation of members, Self-governance and independence, Education, training and information, Cooperation between cooperatives, and Concern for the local community) by relating them to the various cooperative regulations in the agri-food industry. The author focused on a number of laws in this  Act of September 16, 1982, on cooperative law; the Act of  October 4, 2018, on farmers’ cooperatives; the Act of  April 27, 2006, on social cooperatives; the Act of  September 15, 2000, on agricultural producer groups and their associations and amendments to other acts, Act of  February 20, 2015, on renewable energy sources and many others.  In conclusion, the author states that although the principles of cooperation are not explicitly included in Polish legislation, they are implemented and enforced by numerous legal regulations. The implementation of the principles for the establishment and operation of cooperatives in the agri-food sector is linked to the specificities of agriculture. It is possible to observe the influence of the Agricultural Law and the Common Agricultural Policy on the establishment and operation of cooperatives in the agri-food sector. In the author's opinion, the Polish legislator should consider introducing a separate provision on the principles of ICE cooperatives and their characteristics into the Act of 16 September 1982 on Cooperatives.